Cross-disciplinarity in the management of chronic diseases - Lizama Lefno, Andrea (2016)
The health of the human being is a complex phenomenon, essentially multidimensional and provided with a systemic functioning. Thus, health problems cannot be understood in isolation from the gender, race, social and emotional problems or family issues, in short, separated from each person´s history of life and the environment in which they live, because they transcend the purely biological and physiological. Chronic diseases are one of the major health problems in the world, and reflect the impact of modern lifestyle and Western beliefs about life, body and health. The aim of this paper is to analyze the need for medical practice, and particularly the management of chronic diseases, from a systemic health perspective. This implies appealing to a cross-disciplinary perspective, inclusion and integrity in the scientific approach as well, and understanding the various issues of human beings, culture and nature are interconnected and interdependent. Therefore its complexity transcends the division of their physiology and segregation of medical approach, but results in a holistic view of the human being and its health, that understand the human being body and its physiological components as a part of an integrated whole.